A Socio-Legal Approach to Violence Against Women in Nigeria (2015)
Gender constructions are not obvious human categories and factors amongst the most contested academic and scholarly issues. This is partly because gender is a sensitive subject, with varying conceptions dependent on contexts of human actions. Among the most affected subjects of power relations is also gender, thus making it amenable to many interpretations and intervention efforts. Due to the centrality of gender issues to economic, political, social and general practical existences, Nigerian governments over the years have instituted policies and laws to address the issues related to gender. Unfortunately, gender sentiments, biases and orientations that the laws and policies are meant to address also still affect gender constructs and the laws/ policies themselves in a way that calls the policies and the laws to question in terms of efficacy, ultimately. This demonstrates the deepseatedness of gender and its complex yet dynamic nature as it interfaces power and sensitiveness as different categories of humans interact. What is then the place of the laws in addressing gender relations? What are the natures of dominant legal systems in the face of unequal power-play as they affect gender? What are the gaps and the strengths of gender-focused legal systems in Nigeria? Since gender is not a self-evident human category, what are the pathways to a more positive gender relations in Nigeria and how can socio-legal systems more proactively and more positively address gendered human conditions? These are indicative research questions this paper addresses. This paper reviews and analyzes the gender-related components of the Nigerian legal systems and policies in manners that will benefit scholarship and practice.